On a new Agyneta species from Ukraine related to A. suecica Holm, 1950 (Araneae: Linyphiidae) - Gnelitsa, Valery A. (Zootaxa, 2014)
Agyneta pinicola sp.n. is described from Northeastern Ukraine. Agyneta suecica Holm, 1950 is redescribed and a complete comparison of the two species is given.